Corporate Governance Structure and Audit Quality - ZENG, SHIWEN (2012)
Audit quality has always been the focus of attention by government regulatory authorities, the legislature, public investment and other stakeholders. This paper is going to investigate the effects of corporate governance structure on audit quality for the UK evidence. The sample study consists of 226 companies among FTSE 350 listed on the London Stock Exchange (LSE) for the fiscal year of 2011. The regression results and analysis are used to investigate the relationship between the audit quality (as a dependent variable which is measured by the discretionary accruals) and corporate governance structure characteristics as independent variables, including size of board, composition of independent directors, board financial expertise, gender diversity, frequency of board meetings, chairman/ CEO duality and audit committee characteristics including its size, proportion of independent directors, financial expertise and frequency of meetings. The results show that effective boards and audit committees will result in high level of audit quality. In consistent with previous studies, board gender diversity, audit committee independence and audit committee expertise have positive and significant association with audit quality. However, I do not find any significant association between other variables and audit quality. Overall, the findings support regulatory initiatives to improve corporate governance structure and audit quality within organizations.